NEWS. - Carson, A. B. (The Accounting Review, 1961)
Abstract This article presents several news related to accountancy published in the journal of "The Accounting Review." Two substantial contributions to the American Accounting Association Fellowship Fund were accepted on behalf of the Association by President Charles J. Gaa at the annual meeting in Columbus. John P. Goedert, executive partner of Alexander Grant & Company, presented a check for $5,000 contributed by his firm. Mr. Goedert called the contribution a business investment in the future of our profession." He cited recent surveys indicating a shortage of qualified accounting teachers despite large enrollments of students in accountancy and increasing demands for trained accountants by industry, government, and public accounting firms. The accounting research division of the American Institute of Certified Public Accountants has added two items to its active research agenda: Accounting for the Costs of Pension Plans and Cash Flow Statements and Analysis. Anyone interested in submitting comments, suggestions, or other material for the use of the research staff is invited and urged to do so. Advance notice of the intent to participate in the projects in this way will be appreciated. All correspondence relating to the studies should be addressed to Mr. Maurice Moonitz, Director of Accounting Research, American Institute of Certified Public Accountants, 270 Madison Avenue, New York.